1974
DOI: 10.1159/000197573
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative and Prognostic Signs in Acute Hepatic Coma, Treated by Exchange Transfusions

Abstract: Discriminative and prognostic signs in 14 patients with acute hepatic coma, treated by exchange transfusion and permanent intensive care are described. Five patientssurvived and in none of them was there evolution towards cirrhosis. Nine patients diedduring the therapy, without any temporary clinical improvement. The clinical encephalopathy was initially very similar in both groups. Other parameters were, however, different and might have a prognostic value. The arterial blood ammonia and prothrombinvalue were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…Neither the prothrombin value nor blood ammonia differed between those who survived and those who died. This is in accordance with works by Reynolds (1969), and by Saunders et al (1972), but not with that of Demedts et al (1974), who found blood ammonia to be significantly higher in nine patients who died, compared with five patients who survived. Furthermore, the initial prothrombin values were not significantly different but before a third exchange transfusion was performed the prothrombin value (percentage of normal) was significantly higher in the survivors.…”
Section: Discussionsupporting
confidence: 92%
“…Neither the prothrombin value nor blood ammonia differed between those who survived and those who died. This is in accordance with works by Reynolds (1969), and by Saunders et al (1972), but not with that of Demedts et al (1974), who found blood ammonia to be significantly higher in nine patients who died, compared with five patients who survived. Furthermore, the initial prothrombin values were not significantly different but before a third exchange transfusion was performed the prothrombin value (percentage of normal) was significantly higher in the survivors.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that transjugular liver Fulminant liver failure (FLF) is a syndrome associated with a high mortality rate of 65% to 85% (1,2); however, survivors generally recover without sequelae. Various forms of medical treatment have been tried, but none has been shown to alter mortality of FLF (3,4).…”
mentioning
confidence: 99%